Multiple sclerosis treatment and infectious issues: update 2013. (4th February 2014) - Winkelmann, A.; Loebermann, M.; Reisinger, E. C.; Zettl, U. K.
Summary Immunomodulation and immunosuppression are generally linked to an increased risk of infection. In the growing field of new and potent drugs for multiple sclerosis (MS), we review the current data concerning infections and prevention of infectious diseases. This is of importance for recently licensed and future MS treatment options, but also for long‐term established therapies for MS. Some of the disease‐modifying therapies (DMT) go along with threats of specific severe infections or complications, which require a more intensive long‐term monitoring and multi‐disciplinary surveillance. We update the existing warning notices and infectious issues which have to be considered using drugs for multiple sclerosis.